The TOR Pathway Is Involved in Adventitious Root Formation in Arabidopsis and Potato - Deng, Kexuan; Dong, Pan; Wang, Wanjing; Feng, Li; Xiong, Fangjie; Wang, Kai; Zhang, Shumin; Feng, Shun; Wang, Bangjun; Zhang, Jiankui; Ren, Maozhi (Frontiers in Plant Science, 2017)
In the agriculture industry, adventitious root formation is a core issue of plants asexual propagation. However, the underlying molecular mechanism of adventitious root formation is far beyond understanding. In present study we found that target of rapamycin (TOR) signaling plays a key role in adventitious root formation in potato and Arabidopsis. The core components of TOR complex including TOR, RAPTOR and LST8 are highly conserved in potato, but the seedlings of potato are insensitive to rapamycin, implying FK506 Binding Protein 12 KD (FKBP12) lost the function to bridge the interaction of rapamycin and TOR in potato. To dissect TOR signaling in potato, the rapamycin hypersensitive potato plants (BP12-OE) were engineered by introducing yeast FKBP12 (ScFKBP12) into potato. We found that rapamycin can significantly attenuate the capability of adventitious root formation in BP12-OE potatoes. KU63794 (an active-site TOR inhibitor) combined with rapamycin can significantly suppress adventitious root formation of BP12-OE potato, indicating its synergistic inhibitory effects on potato adventitious root formation. Furthermore, RNA-seq data showed that many genes associated with auxin signaling pathway were altered when BP12-OE potato seedlings were treated with rapamycin + KU, suggesting that TOR may play a major role in adventitious root formation via auxin signaling. The auxin receptor mutant tir1 were sensitive to TOR inhibitors and the double and quadruple mutants including tir1afb2, tir1afb3 and tir1afb1afb2afb3 displayed more sensitive to asTORis than single mutant tir1. Consistently, overexpression of AtTIR1 in Arabidopsis and potato can partially overcome the inhibitory effect of asTORis and promote adventitious root formation under asTORis treatments. These observations suggest that TOR signaling regulates adventitious root formation by mediating auxin signaling in Arabidopsis and potato.